Toy photography as a visual representation of the life forms around the world's highest navigable lake Titicaca - Yucra Mamani, Yudi Janeh; Aragón Cruz, Walker Ernesto (Street Art & Urban Creativity, 2025)
This study aims to explore the use of toy photography as a visual representation of the ways of life around Lake Titicaca in Puno (Peru). The research is qualitative and employs the technique of photographic discourse analysis. The research corpus consists of 145 photographs recorded by students from the Social Communication Sciences program at the National University of Altiplano Puno (UNAP), who visually represented the different ways of life around Lake Titicaca using their mobile devices. The results show that toy photography became an innovative resource, through which thematic categories emerged that reflect everyday life, cultural manifestations, aquatic and terrestrial fauna, tourism activities, means of transportation, and environmental issues such as pollution and global warming. It is concluded that toy photography facilitates the representation of real and imagined visual narratives that playfully capture the essence of their photographic proposal.